Factors associated with therapy non-completion for children with problematic sexual behaviors - Camille Pitre; Isabelle Daignault; Stéphanie Chouinard Thivierge; Marc Tourigny (Frontiers Media S.A., 2024)
IntroductionChildren with problematic sexual behaviors (PSBs) can benefit, along with their parents or caregivers, from specialized therapeutic services to limit the manifestation of these behaviors. However, for some families, mobilization for therapy represents a significant challenge since a considerable proportion do not complete the therapy intended for them. The present study aims to identify the factors associated with therapy completion, thus allowing a deeper understanding of how to support children and more broadly families to complete their therapeutic process.MethodologyThe sample consists of 67 caregiver-child dyads referred to a specialized Center offering PSBs-focused cognitive behavioral therapy, actively involving the caregiver. Standardized questionnaires were administered to children and their caregiver before and after the therapy.ResultsWhile non-completers represent 31% of our sample, they present very similar profiles to completers in terms of socio-demographic characteristics, behavior problems and symptoms. However, they appear to differ regarding living situations and coping mechanisms. Results show that children who complete therapy are more likely to live in a placement situation, compared to non-completers. Children who completed therapy also report using more coping strategies that aim toward getting social support and less distancing coping strategies than non-completers. Non completers also reported feeling less maternal support compared to completers.DiscussionResults underline the importance of implementing mobilization efforts for families with children with PSBs, along with a focus on developing efficient coping mechanisms.